GAMBARAN PENGETAHUAN PERAWAT TENTANG DISCHARGE PLANNING - Shinta Sandora; Noraliyatun Jannah; Racmah Racmah (Jurnal Ilmiah Mahasiswa Fakultas Keperawatan, 2022)
Discharge planning is an ongoing assessment to obtain comprehensive information about patient needs according to nursing diagnosis statements, planning to ensure patient needs carried out by health service providers. The implementation of discharge planning given by nurses is the understanding possessed by nurses, education, motivation in nurses, and the communication used. The purpose of the case study is to identify a description of nurses' knowledge about the implementation of discharge planning in the inpatient ward of the Banda Aceh hospital. The study population was 22 nurses. The case study uses a nursing knowledge questionnaire against the implementation of discharge planning in a Banda Aceh hospital. Based on the results of the case study, it can be concluded that the description of nurses' knowledge about discharge planning is sufficient (54.6%), and the results of nurses' understanding of the meaning of discharge planning are balanced between good and sufficient (50%), nurses' understanding of the purpose of discharge planning is in the category enough (54.5%), nurses' understanding of discharge planning principles was in the sufficient category (54.6%), and nurses' understanding of the discharge planning implementation process was in the sufficient category (72.8%).